Strategi Pengembangan Daya Tarik Kota Lasem Sebagai Kota Batik-Kopi - Tangguh Okta Wibowo (Jurnal Pariwisata Terapan, 2018)
This article explores about the tourism potency of Lasem city, a district located in Rembang Regency, Central Java. Data are collected from information circulating on the internet, some testimonials from blogs, and also observations from researchers directly. This article uses city branding theory to explore tourist destination and to maximize the potential things that can be developed. From the results of  discussion, the strategies for developing Lasem city to attract many visitors are to formulate a new city branding for Lasem city supported by the development of infrastructure for supporting a city branding: the Lasem as Batik-Coffee City.